An example of the analysis of climate change in agriculture using Griffiths-Taylor diagrams - Tjaša POGAČAR; Zoja GAŠPARIČ; Lučka KAJFEŽ BOGATAJ; Zalika ČREPINŠEK (Acta Agriculturae Slovenica, 2022)
The climate clearly determines the characteristics of agriculture in terms of favourable conditions for the development of plants and animals. Climate change has a major impact on agriculture, and we need at least its analysis for past decades for effective adaptation. The annual scale of meteorological variables is quite rough, much more information is obtained from the monthly scale, for example when using bioclimatic indices and diagrams. Using Griffiths-Taylor diagrams, where each point shows the average monthly value of temperature and relative humidity or precipitation, we showed the change of 30-year averages (1961 to 2020) for six climate stations. Climate change can be seen from the shape of the diagram, an increase in average monthly air temperatures, a decrease in average relative humidity and changed precipitation patterns are visible. With the plot of favourable conditions for a certain plant / animal species, the diagram acquires ecological value. We have shown changes in the conditions for the development of the fruit fly (Ceratitis capitata (Wiedemann, 1824)) and the growth of sweet potatoes (Ipomoea batata L.). For the fruit fly, conditions improved due to higher temperatures, especially in colder locations. In Murska Sobota, which has the only suitable conditions for the growth of sweet potatoes, the period with favourable conditions is extended, in the last two periods in July and August, ideal conditions also appear. In further research, we recommend an analysis of weather-extreme years, which provides additional information on the variability of the conditions.